Chlorine Demand and Inactivation of Fungal Propagules - Rosenzweig, W. D. (1983)
Conidia of filamentous fungi, vegetative yeast cells, and coliform bacteria were tested to determine their chlorine demand and their sensitivity to chlorine inactivation. Levels of chlorine demand for the various conidia, yeast, and coliforms were, respectively, 3.6 × 10(−9) to 3.2 × 10(−8), 1.2 × 10(−9) to 8.0 × 10(−9), and 2.5 × 10(−11) to 6.3 × 10(−10) mg of chlorine per propagule. Preliminary evidence suggests that the chlorine demand per propagule increases as the number of propagules per milliliter decreases. In general, conidia showed greatest resistance to chlorine inactiviation, followed by the yeast and coliforms. Inactivation by chlorine was influenced by pH, with inactivation (chlorine activity) falling in the order pH 5 > 7 > 8.